تحليل العوامل المؤثرة في تغيير المراجع الخارجي ( دراسة ميدانية فى المصارف الواقعه بمناطق الجميل، رقدالين و زلطن) (Comprehensive Journal of Science, 2025)
The study aimed to identify the importance of analyzing the most important factors influencing the change of the external auditor by managers and financial managers in bank branches in the areas of Al-Jamil, Ragdalin and Zliten. To achieve the objectives of the study, a survey sheet was designed consisting of several paragraphs that included basic axes, which are the elements related to the factors of changing the external auditor. (12) survey sheets were distributed in order to test the study hypothesis and from there reach results that can be generalized to the study community in a way that serves the objectives of the study. The descriptive approach was used to describe the definition of changing the external auditor, its advantages and disadvantages, in addition to factors specific to the management of joint-stock companies (banks), factors related to the desire to switch to a specific auditor, and factors specific to the external auditor's report to identify the most important factors related to changing the external auditor. The data obtained through the survey sheet was analyzed using the Statistical Package for the Social Sciences (SPSS), where the arithmetic mean, standard deviation, and a one-sample T-test were used. The results showed that there is a set of factors specific to changing the external auditor, including those related to company management, factors related to the desire to switch to a specific auditor, and factors specific to the external auditor's report. This was from the perspective of managers and financial directors at the bank branches in the areas of El-Gamil, Ragdalin, and Zliten..
Keywords: Changing the external auditor, advantages of changing the external auditor, disadvantages of changing the external auditor, factors specific to the management of joint-stock companies (banks), external auditor's report, factors specific to the desire to switch to a specific external auditor